Misery index : theory and application to Singapore. - Lin, Jiehui. (2013)
The purpose of this paper is to develop a suitable misery index for Singapore. The index is used to capture the movements of the aggregate demand (AD) curve and prevent the government from engaging in soft-options trade-offs between inflation and unemployment. Numerous models will be discussed and tested for their reliability using simple linear regression. Our regression results showed that the unweighted misery index is unreliable for Singapore. Other models like the Augmented and Barro misery index were found to be reliable but the values of these models might capture the movements of the aggregate supply (AS) curve as well. The misery index should only include additional variables that would depict the trade-offs from the government’s use of soft-options. We further examined the possibility of Singapore’s foreign labour policy as a soft-option but due to various limitations, we were unable to prove this hypothesis. We also examined the influence of rental income on Singaporeans’ perception on inflation. We found that a small proportion of households have rental income, which does not alter the weightage of inflation in the index. Further evaluation revealed a suitable weightage for Singapore’s misery index of at least 5:1 to unemployment and inflation respectively.